Characterisation and milling time optimisation of nanocrystalline aluminium powder for selective laser melting. Issue 5 (February 2017) - Han, Quanquan; Setchi, Rossitza; Evans, Sam
Abstract The aim of this study is to investigate the properties of high-energy ball-milled nanocrystalline aluminium powders and to determine the optimum milling time required to produce an advanced aluminium powder for selective laser melting (SLM). Previous research has indicated that powders suitable for SLM include milled nanocrystalline aluminium powders with an average grain size of 60 nm and good flowability (Carr index less than 15 %). This study employs advanced nanometrology methods and analytical techniques to investigate the powder morphology, phase identification, average grain size and flowability of ball-milled powders. Stearic acid is used to prevent excessive cold welding of the ball-milled powder and to reduce abrasion of the grinding bowl and balls. The results indicate that, whilst the average particle size achieves a steady state after 14 h of milling, the grain size continues to decrease as the milling time progressed (e.g. the transmission electron microscopy measured average grain size is 56 nm after 20 h of milling compared to 75 nm for 14 h of milling). The aluminium powders milled for 16 and 20 h exhibit good flow behaviour, achieving a Carr index of 13.5 and 15.8 %, respectively. This study shows that advanced nanocrystalline aluminium powders suitable for SLM require ball milling for between 16 and 20 h, with 18 h being the optimum milling time.